Oil & Ethnocentrism: A study of Global Oil & Gas Organisations - Rees, Gareth (2014)
This dissertation will examine the concept of ‘ethnocentrism’, or a belief in the superiority of one’s own cultural norms and values, against the backdrop of the Global Oil & Gas Service industry. Using Howard Perlmutter’s framework, ethnocentrism will be tested and analysed across distinct areas of international business; staffing and cultural prevalence, the management of international subsidiaries and corporate and national culture.